2014
DOI: 10.1210/en.2013-1800
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Alterations in Thyroid Hormone Homeostasis in Combined Mct10 and Mct8 Deficiency

Abstract: The monocarboxylate transporter Mct10 (Slc16a10; T-type amino acid transporter) facilitates the cellular transport of thyroid hormone (TH) and shows an overlapping expression with the well-established TH transporter Mct8. Because Mct8 deficiency is associated with distinct tissue-specific alterations in TH transport and metabolism, we speculated that Mct10 inactivation may compromise the tissue-specific TH homeostasis as well. However, analysis of Mct10 knockout (ko) mice revealed normal serum TH levels and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 38 publications
7
66
1
Order By: Relevance
“…The values which we obtained were in general higher than those observed by investigators who used immunological methods [12,13,14,15,24,25,26,27], possibly due to the higher accuracy of the MS technique. Galton et al [28] reported similar or higher concentrations in kidney and liver, but in that study the homogenates were incubated with β-glucuronidase and therefore tissue concentrations also included glucuronide conjugates of THs.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…The values which we obtained were in general higher than those observed by investigators who used immunological methods [12,13,14,15,24,25,26,27], possibly due to the higher accuracy of the MS technique. Galton et al [28] reported similar or higher concentrations in kidney and liver, but in that study the homogenates were incubated with β-glucuronidase and therefore tissue concentrations also included glucuronide conjugates of THs.…”
Section: Discussioncontrasting
confidence: 86%
“…As a matter of fact, complex changes in serum and tissue TH concentrations have recently been described in mice showing MCT8 and/or MCT10 deficiency [27], although it has been reported that the thyroid state had little effect on the transcription of T 4 transporters, at least in the liver [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on adult Mct8-knockout mice showed that T3 levels were elevated not only in the liver but also in the kidney (15,16). In agreement with the findings observed in mice treated chronically with T3, TRb expression was significantly decreased in the liver but not in the kidney in Mct8-knockout mice (Fig.…”
Section: Adaptations During Hyperthyroidism and Withdrawal 855supporting
confidence: 89%
“…Mct8 has been reported to have a greater impact on TH efflux than influx in liver cells, as Mct8 -/y mice have higher T 3 content in liver and show upregulated Dio1 expression and activity [14][15][16] . Similarly Mct10 has been proposed to mediate TH efflux in liver tissue [16] . However, in our study the extent of regulation of both transporters remained in a significant range in livers of old mice only.…”
Section: Discussionmentioning
confidence: 99%